2014
DOI: 10.1002/mc.22128
|View full text |Cite
|
Sign up to set email alerts
|

Potentially functional polymorphisms in aminoacyl-tRNA synthetases genes are associated with breast cancer risk in a Chinese population

Abstract: Aminoacyl-tRNA synthetases (ARSs) are responsible for cellular protein synthesis and cell viability involving in various process of tumorigenesis. We hypothesized that genetic variants in core ARSs genes may play an important role in the development of breast cancer. Thus, we conducted a case-control study including 1064 breast cancer cases and 1073 cancer-free controls to evaluate the associations of 28 potentially functional polymorphisms in 12 core ARSs genes (AARS, CARS, EPRS, HARS, KARS, LARS, MARS, QARS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…Several studies have now shown that for YARS, GARS, and AARS loss of aminoacylation is, in fact, not necessary for the disease to develop [Antonellis and Green, 2006; Nangle et al, ; Storkebaum et al, ; McLaughlin et al, ]. Instead, these and other recent studies suggest a mechanism related to either a dominant‐negative effect on the holoenzyme or interference with secondary functions [Jordanova et al, ; Motley et al, ; Vester et al, ; Grice et al, ; He et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have now shown that for YARS, GARS, and AARS loss of aminoacylation is, in fact, not necessary for the disease to develop [Antonellis and Green, 2006; Nangle et al, ; Storkebaum et al, ; McLaughlin et al, ]. Instead, these and other recent studies suggest a mechanism related to either a dominant‐negative effect on the holoenzyme or interference with secondary functions [Jordanova et al, ; Motley et al, ; Vester et al, ; Grice et al, ; He et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the upregulation of aaRSs, including YARS, was observed in several types of cancer (Guo et al 2010;Hsu et al 2019), while polymorphisms in aaRS genes were reported to be associated with breast cancer risk (He et al 2015). Emerging studies also implicated the involvement of aaRSs with multiple pathway networks through constituting the multi-tRNA synthetase complex (MSC) (Hyeon et al 2019) and raised the possibility of aminoacyl-tRNA synthetases as therapeutic targets against autoimmune diseases, rare diseases, and even cancer (Kwon et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that about 3.2 million people will be diagnosed with breast cancer each year by 2050 worldwide [3]. Breast cancer is a complex and multifactorial disease, which is affected by combined effects of environmental and inherited factors [4]. It is characterized by starting with hyperplasia, in distinct steps, in situ ductal and invasive carcinoma then evolv-ing into a deadly metastatic disease [5].…”
mentioning
confidence: 99%